Role of j-domain proteins in yeast physiology and protein quality control - Ruger-Herreros, Carmen; Svoboda, Lucia; Mogk, Axel; Bukau, Bernd (Journal of molecular biology, 2024)
The Hsp70 chaperone system is a central component of cellular protein quality control (PQC) by acting in a multitude of protein folding processes ranging from the folding of newly synthesized proteins to the disassembly and refolding of protein aggregates. This multifunctionality of Hsp70 is governed by J-domain proteins (JDPs), which act as indispensable co-chaperones that target specific substrates to Hsp70. The number of distinct JDPs present in a species always outnumbers Hsp70, documenting JDP function in functional diversification of Hsp70. In this review, we describe the physiological roles of JDPs in the Saccharomyces cerevisiae PQC system, with a focus on the abundant JDP generalists, Zuo1, Ydj1 and Sis1, which function in fundamental cellular processes. Ribosome-bound Zuo1 cooperates with the Hsp70 chaperones Ssb1/2 in folding and assembly of nascent polypeptides. Ydj1 and Sis1 cooperate with the Hsp70 members Ssa1 to Ssa4 to exert overlapping functions in protein folding and targeting of newly synthesized proteins to organelles including mitochondria and facilitating the degradation of aberrant proteins by E3 ligases. Furthermore, they act in protein disaggregation reactions, though Ydj1 and Sis1 differ in their modes of Hsp70 cooperation and substrate specificities. This results in functional specialization as seen in prion propagation and the underlying dominant role of Sis1 in targeting Hsp70 for shearing of prion amyloid fibrils.